Linking ages – un/doing age and family in the Covid-19 pandemic - Grit Höppner (University of Bamberg Press, 2021)
Objective: In this paper we ask how and through which social practices age and family are relationally being un/done in the course of the pandemic in Germany, and how these un/doings shape, shift or even break intergenerational relations.